"INFLUENCE OF BASIC MOTOR ABILITIES AND CONOTIVE CRITERION ON RESULTS OF SUCCESS IN SOME SPORTS GAMES FOR STUDENTS OF TEACHING SCHOOL" - Midhat Mekić; Rašid Hadžić; Edin Mirvić; Osman Bukvić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Upon the results of research it is possible to conclude that high level of influence of basic motor abilities and conotive criterion for successive results of sports games. Dominative predictions of values had conatice characteristic (A1,L17) and one test for judgment of explosiveness of lower extremities. For above mentioned results of this research, first of all, main values of defining hypothesis for further research, as well as promotion of education-teaching process of sports games in high schools.